2012
DOI: 10.5539/ass.v8n10p16
|View full text |Cite
|
Sign up to set email alerts
|

Stress Testing of Commercial Banks’ Exposure to Credit Risk: A Study Based on Write-off Nonperforming Loans

Abstract: This study introduced a stress-testing model with a dummy variable that refers to write-off non-performing loans (NPL) by Agricultural Bank of China. A new variable Y that indicated the rate of NPL in major national commercial banks in terms of logit transformation was applied to test stress tolerance. This article built a regression model on the basis of four explanation variables: the growth rate of GDP, indicator of customer price, the growth rate of supplying nominal currency and indicator of house price. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
1
0
2
Order By: Relevance
“…Foglia (2009) reviews macro stress testing methods developed at selected central banks and supervision authorities for stress testing the credit risk of banks using bank-specific measures of credit risk as inputs. Lu and Yang (2012) uses a vector autoregression method to find key predictive variables of non-performing loans in Chinese commercial banks. They concluded that lower growth rate of GDP, slump in CPI, slowdown in supply of nominal currency, and residential property prices were key predictors.…”
Section: Limmentioning
confidence: 99%
“…Foglia (2009) reviews macro stress testing methods developed at selected central banks and supervision authorities for stress testing the credit risk of banks using bank-specific measures of credit risk as inputs. Lu and Yang (2012) uses a vector autoregression method to find key predictive variables of non-performing loans in Chinese commercial banks. They concluded that lower growth rate of GDP, slump in CPI, slowdown in supply of nominal currency, and residential property prices were key predictors.…”
Section: Limmentioning
confidence: 99%
“…A medida mais comum para mensuração do risco de crédito é a inadimplência de uma carteira, que pode ser definida como: (1) a quantidade de contratos ou clientes que não cumpriram com suas obrigações em relação à quantidade total de contratos em uma data base (MISINA et al, 2006;END, VAN DEN et al, 2006;FANG-YING, 2011;VAZQUEZ et al, 2012;LU;YANG, 2012); (2) o saldo dos contratos em atraso em relação ao saldo total dos contratos em uma data base (HOGGARTH et al, 2005) ou 3o número de empresas em falência em relação ao número total de empresas de sua carteira em uma data base (VLIEGHE, 2001;BUNN et al, 2005), entre outros. A inadimplência desempenha um papel importante nas decisões relacionadas a crédito nas instituições financeiras (CORREA et al, 2011).…”
Section: Revisão Bibliográficaunclassified
“…, construção de um modelo ARIMAX que foi utilizado como benchmark (JONES; HILBERS;SLACK, 2004;SORGE;VIROLAINEN, 2006; FANG-YING, 2011;LU;YANG, 2012;SCHECHTMAN;GAGLIANONE, 2012), obtenção de fatores por meio da análise fatorial, construção de um modelo ARIMAX com os fatores como variáveis explicativas, construção de um modelo de defasagem distribuída polinomial com as variáveis macroeconômicas como variáveis explicativas e, por último, a performance dos modelos propostos é comparada à do modelo benchmark para o período de validação. Na Figura 3 é colocado o resumo do processo de pesquisa para a identificação das vulnerabilidades do sistema financeiro.…”
unclassified